2016
DOI: 10.4236/ae.2016.41001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Human Landing Catch and CDC Light Trap in Mosquito Sampling in Knowlesi Malaria Endemic Areas in Peninsula Malaysia

Abstract: Adult mosquito sampling techniques are essential for monitoring transmission of malaria and other mosquito borne infections. Preference for any sampling technique depends on both its field efficiency and the characteristics of local vector populations. Surveys on adult mosquitoes using Human Landing Catch (HLC) and CO2-baited CDC light trap (CDC-LT) techniques were conducted in several knowlesi malaria endemic areas between the months of March to December 2012 in several states of Peninsula Malaysia. These two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…using CDC light traps [ 44 ]. Our findings were also in agreement with the previous study by Rohani et al (2016) where HLC had a better ability to catch these three species of Anopheles mosquitoes compared to CO 2 baited CDC light traps [ 24 ]. However, in their study, An.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…using CDC light traps [ 44 ]. Our findings were also in agreement with the previous study by Rohani et al (2016) where HLC had a better ability to catch these three species of Anopheles mosquitoes compared to CO 2 baited CDC light traps [ 24 ]. However, in their study, An.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies had previously evaluated different trapping methods for monitoring malaria vectors. These include the conventional trapping methods such as CDC light traps [ 24 ], human-baited double net (HDN) traps [ 25 ], BG-malaria traps [ 38 , 39 ] and monkey-baited traps [ 40 ] as well as some of the latest methods, including M-Tego [ 41 ], Suna traps [ 42 ] and electric nets [ 43 ]. All these studies agree that different sampling techniques influence the quantity and diversity of the mosquitoes collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, out of thousands of mosquitoes collected, only a single resting Anopheles mosquito was successfully obtained from each study. Other methods available to collect non-resting mosquitoes for blood meal analysis such as CDC light traps are inefficient at collecting Anopheles mosquitoes from the Leucosphyrus Group compared to human landing catch (HLC) 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that light trap is not as efficient as human landing catch method (Rohani et al . 2015). Both human landing catches and monkey-baited traps come with associated ethical problems yet for these particular vector species light traps do not provide a good alternative method.…”
Section: Challenges Associated With Vector Studiesmentioning
confidence: 99%